Síndrome de Arboleda-Tham causado por nova variante genética - Ivana Cardoso; Margarida Fernandes; Rita Quental; Marta Vila Real; Fátima Santos (Sociedade Brasileira de Pediatria, 2023)
We report the case of a 10-year-old boy followed since birth due to a polymalformative syndrome, including congenital cardiac disease, microcephaly, failure to thrive, trunk hypotonia and hypertonia of the extremities. With time, chief complaints were developmental delay and absence of expressive language. On physical examination dysmorphic facial features became more evident. The chromosomal analysis and array comparative genomic hybridization (aCGH) revealed no significant pathogenic changes. Whole Exome Sequencing (WES) identified the likely pathogenic variant c.4027dup p.(Glu1343Glyfs*13) in heterozygosity in KAT6A gene. This variant results in the production of a truncated protein and was not reported previously in the literature. Pathogenic variants in the KAT6A gene cause Arboleda-Tham Syndrome (ARTHS), which has variable clinical presentations. This boy´s features and severe developmental defects are compatible with the ones described in other cases of late-truncating pathogenic variants in this gene. Reviewing the literature, we found out that this is the first patient in Portugal diagnosed by WES and that it involves a novel reported genetic variant.